TINGKAT AKTIVITAS FISIK DAN STATUS GIZI SISWA SEKOLAH DASAR DI KOTA SURABAYA PASCA PTM 100% PANDEMI COVID-19 - Rizkanto, Billy Emir; Hayati, Hayati; Anisa, Putri Juliah; Anwar, Shinta Nuriyah; Harun, Harun (Journal of Sport and Exercise Science, 2023)
Covid-19 pandemic had an effect on students tegarding changes in sedentary lifestyle during studying at home, coupled with advances in technology which has caused student to prefer games that less phsycal activity, this is feared to still be a habit for students, after covid-19 pandemic. Studying at school that has been proclaimed by  Surabaya government, causing a decrease an increased risk of obesity in student. Therefore this study aims to provide an overview the physical activity level and nutritional status of elementary school in Surabaya. this study were examining nutritional status through Body Mass Index and physical activity level using (IPAQ) for student in three elementary schools in Surabaya. the average nutritional status of student based on BMI/age is 19,5±4,02,  1,02% severely thinnes, 21,94% thinnes 56,63% normal, 16,83% overweight and 3,57% obese, the average level of physical activity is 1037±851 MET-min/week, 46,42% low, 40,81% moderate, 12,75% high. This shows that elementary school student in Surabaya have good nutritional status but have a level activity that tends to be less.